Digital Skills in the EU: Cluster Analysis - Velichkov, Nikolai; Stefanova, Kristina (Research Papers, 2018)
This paper aims at drawing the distinctions between European Union member states with respect to the digital skills of the population along with identifying similarities among the different countries comprising a common model. The results of the applied cluster analysis method reveal that the degree of digital competence can be perceived as an important model-defining characteristic for the differentiation of individual models within the EU. At the same time, the obtained results demonstrate the existence of similarities among countries with relatively close geographic location and similar degree of economic development.